KINETICS OF PIROXICAM RELEASE THROUGH IONTOPHORESIS AT VARIOUS PHS FROM POLYELECTROLYTE HYDROGELS WITH SODIUM ALGINATE-TRAGACANTH GUM POLYMER - Nining, Nining; Fith Khaira Nursal; Abu Rijal Algifari (Jurnal FARMASIMED (JFM), 2023)
Piroxicam is a non-steroidal anti-inflammatory drug (NSAID) used to treat symptoms of osteoarthritis and rheumatoid arthritis. This drug can irritate the stomach as a side effect of oral administration. One strategy to overcome these side effects is transdermal delivery in polyelectrolyte hydrogel with iontophoresis. This research aims to study the pH-varying effect of polyelectrolyte hydrogel on piroxicam release from hydrogel via iontophoresis using a Franz diffusion cell. The formulation was made with pH variations, namely 4.2 (F1), 5.5 (F2), 6.4 (F3), and 7.4 (F4). Evaluations include organoleptics, pH, homogeneity, spreadability, viscosity, flow properties, conductivity, and diffusion tests. The polyelectrolyte hydrogel obtained was yellow and homogeneous with a pH variation of 4.2 ± 0.02 to 7.42±0.02, spreadability of 4.22±0.21 cm to 4.35±0.28 cm, viscosity 47,378 cps to 59,297 cps; flow properties include thixotropic plasticity; and conductivity 8.01±0.78 ms/cm to 9.58±1.00 ms/cm. Moreover, piroxicam was released from the hydrogel assisted by DC-type iontophoresis with flux values of 634.52 ?g/cm2 (F1), 427.91 ?g/cm2 (F2), 205.76 ?g/cm2 (F3), and 253.56 ?g/cm2 (F4). Statistical analysis showed that decreasing pH had a significant effect (sig<0.05) on increasing piroxicam release from hydrogel based on flux value. The release kinetic behavior of all formulas (F1-F4) does not show the same type of kinetic model based on the correlation coefficient value approach, which is closest to 1. Keywords: Diffusion, flux, drug release, release kinetics.